Phenolic Content of Hypodaphnis Zenkeri and Its Antioxidant Effects against Fenton Reactions' Mediated Oxidative Injuries on Liver Homogenate - Bruno Moukette Moukette; Constant Anatole Pieme; Prosper Cabral Nya Biapa; Jacques Romain Njimou; Vicky Jocelyne Ama Moor; Marco Stoller; Marco Bravi; Jeanne Yonkeu Ngogang (MDPI AG, 2014)
Under oxidative stress conditions, endogenous antioxidant defenses are unable to completely inactivate the free radicals generated by an excessive production of reactive oxygen species (ROS). This state causes serious cell damage leading to a variety of human diseases. Natural antioxidants can protect cells against oxidative stress. Hypaodaphnis zenkeri (H. zenkiri) is a plant consumed as a spice in the Cameroonian diet, and its bark has been used in traditional medicine for the treatment of several diseases. The present study aims at investigating the antioxidant activity, which includes free radical scavenging and protective properties of an extract from H. Zenkiri against oxidative damage on a liver homogenate. The free radical assays determined the scavenging activities of 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl (OH), nitrite oxide (NO) and 2,2-azinobis(3-ethylbenzthiazoline)-6-sulfonic acid (ABTS) radicals and the enzymes, whose protection was to be considered in the liver homogenate, including superoxide dismutase, catalase, and peroxidase. The antioxidative activities were studied using the ferric reducing antioxidant power (FRAP), reductive activity, and phosphomolybdenum antioxidant power (PAP) methods. In addition, the phenolic contents of the extracts were examined. The results showed that these extracts demonstrated significant scavenging properties and antioxidant activities, with the hydro-ethanolic extract of the bark of H. zenkeri (EEH) being the most potent. This extract had the highest total polyphenol (21.77 ± 0.05 mg caffeic acid (CAE)/g dried extract (DE)) and flavonoids (3.34 ± 0.13 mg quercetin (QE)/g dried extract) content. The same extract had significantly greater protective effects on enzyme activities compared to other extracts. The high performance liquied chromatography (HPLC) profile showed higher levels of caffeic acid, OH-tyrosol acid, and rutin in the leaves compared to the bark of H. zenkeri. In conclusion, the ethanolic and hydro-ethanolic extracts of the bark and leaves from H. zenkeri showed an antioxidant and protective potential against oxidative damage.